Pengaruh Kualitas Kerja Pegawai dan Disiplin Kerja terhadap Prestasi Kerja Pegawai pada PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Ciracas - Afiefah Nurmaulida; Aswin Naldi Sahim; Irawan R. D Budianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Organizational effectiveness is heavily influenced by employee performance, especially in state-owned businesses that focus on providing services. However, achieving optimal performance may be hampered by employee variances in job quality and discipline. The purpose of this study is to examine the partial and simultaneous effects of work quality and work discipline on employee performance at PT PLN (Persero) Customer Service Implementation Unit (UP3) Ciracas. This study used a survey method and a quantitative associative methodology. A census was employed as the sample method, and the population comprised all 54 UP3 Ciracas personnel. With the use of SPSS version 26, data were gathered using structured questionnaires and subjected to multiple linear regression analysis. The findings show that employee performance is positively and significantly impacted by job quality, indicating a considerable contribution to performance enhancement. Employee performance is positively and significantly impacted by work discipline as well. Employee performance is strongly impacted by both work quality and work discipline at the same time, suggesting that both factors are strategically important for improving work outcomes. These results imply that maintaining employee discipline and enhancing work quality are crucial managerial initiatives to raise employee performance inside the company.